2021
DOI: 10.3390/polym13132101
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Hazards of Giant Reed (Arundo donax L.) in the Macaronesia Region and Its Characterisation as a Potential Source for the Production of Natural Fibre Composites

Abstract: This paper summarises the results obtained from the characterisation of giant reed (Arundo donax L.) plant and fibres. The research is part of a project developed in the Macaronesia region, of which the aim is to demonstrate the feasibility of using biomass from invasive plant species in the composites sector as a way of financing control campaigns and habitats conservation labours. An experimental procedure for the extraction of fibre bundles from this plant was developed, and the material obtained was charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…compares the elastic modulus in this study and those reported in the literature. [31,34,35,39,45,47,[54][55][56][57][58][59][60][61][62][63] The mechanical properties of the PBAT composites prepared with largesize reeds in this study were much better than those reported in the literature for the powder-filled biomass. However, with the use of reed at 30%, the tensile strength, elongation, and impact properties of the composites decreased from 16.5 ± 0.1 MPa, 822.0 ± 0.1%, and 26.2 ± 1.1 kJ/m 2 to 11.9 ± 0.2 MPa, 27.9 ± 1.8%, and 17.6 ± 0.9 kJ/m 2 .…”
Section: Properties Of Pbat/reed Compositesmentioning
confidence: 87%
See 1 more Smart Citation
“…compares the elastic modulus in this study and those reported in the literature. [31,34,35,39,45,47,[54][55][56][57][58][59][60][61][62][63] The mechanical properties of the PBAT composites prepared with largesize reeds in this study were much better than those reported in the literature for the powder-filled biomass. However, with the use of reed at 30%, the tensile strength, elongation, and impact properties of the composites decreased from 16.5 ± 0.1 MPa, 822.0 ± 0.1%, and 26.2 ± 1.1 kJ/m 2 to 11.9 ± 0.2 MPa, 27.9 ± 1.8%, and 17.6 ± 0.9 kJ/m 2 .…”
Section: Properties Of Pbat/reed Compositesmentioning
confidence: 87%
“…Comparison of elastic modulus of PBAT composites in our study and literature. [31,34,35,39,45,47,[54][55][56][57][58][59][60][61][62][63] (B) Comparison of tensile strength and elongation of PBAT composites in our study and literature. [36,41,47,54,62,64,65] patterns of PBAT and its composites.…”
Section: Properties Of Pbat/reed Compositesmentioning
confidence: 99%
“…At the same time, the matrix is responsible for arresting cracks from propagation between fibers and holding fibers in the proper orientation, protecting fibers from the environment, and more importantly, transferring the load from the broken fibers to their neighboring intact fibers through the interface. 513…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the matrix is responsible for arresting cracks from propagation between fibers and holding fibers in the proper orientation, protecting fibers from the environment, and more importantly, transferring the load from the broken fibers to their neighboring intact fibers through the interface. [5][6][7][8][9][10][11][12][13] Natural fibers have attracted increased interest in the last decade as a substitute for glass fibers in composite components, especially in the housing sector. Fibers like jute, sisal, coconut fiber (coir), ramie, banana, flax, hemp, and so on, are cheap, have better stiffness per unit weight, and have a lower environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ortega et al produced composites with 5% w/w of banana and abaca fibers with significant improvements in mechanical properties, except for impact strength [18], while Hejna et al obtained composites with up to 20% w/w of wheat bran, although only those with up to 5% content did not show significant loss of mechanical properties [1]. Buckwheat husk, reed, or bamboo are other materials proposed to broaden the options of using lignocellulosic materials [13,16,19,20]. Other authors introduced in rotomolded parts some fillers traditionally considered waste materials, such as cable covers [21] or copper slag from mining [2].…”
Section: Introductionmentioning
confidence: 99%